FIKIH MINORITAS DAN IMPLEMENTASINYA DALAM KEHIDUPAN MUSLIM MINORITAS DI LINGKUNGAN MULTIKULTURAL - Siti Khofifah; Abdul Wahid Haddade; Patimah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to examine the urgency, principles, and application of fiqh al-aqalliyyāt (fiqh of Muslim minorities) within multicultural societies, particularly in maintaining harmonious interfaith relations. The research employs a qualitative library-based research design by analyzing classical and contemporary Islamic legal sources, scholarly opinions, fatwas, and relevant literature to understand how Islamic law responds to the challenges faced by Muslims living as minorities in non-Muslim-majority countries. Data were collected through systematic document analysis of fiqh texts, the maqāṣid al-sharīʿah framework, and contemporary fatwa institutions such as the European Council for Fatwa and Research. The findings indicate that fiqh al-aqalliyyāt functions as a contextual and adaptive legal framework that emphasizes the principles of facilitation (taysīr), removal of hardship (rafʿ al-ḥaraj), public interest (maṣlaḥah), and consideration of legal consequences (maʾālāt). This approach enables Muslim minorities to fulfill their religious obligations while engaging constructively within diverse social, cultural, political, and religious environments. The study further reveals that the novelty of fiqh al-aqalliyyāt lies in its integrative methodology, which combines classical juristic principles with contemporary social realities, thereby offering practical solutions to issues such as interfaith greetings, religious practices, economic transactions, and political participation. The implications of this research underscore the importance of fiqh al-aqalliyyāt as a reference for the development of Islamic law, the strengthening of interfaith harmony, and educational discourse on Islam in multicultural contexts, contributing to a more inclusive and context-sensitive understanding of Islam in the modern era.